The onset of Type 3C diabetes mellitus in a young female due to distal pancreatectomy for solid pseudopapillary neoplasm - Ayaka Harada; Takatoshi Anno; Kohei Kaku; Hideaki Kaneto (Endocrinology, Diabetes & Metabolism Case Reports)
Solid pseudopapillary neoplasm (SPN) is classified as an epithelial tumor identified from benign to low-grade malignant tumor. It is a relatively rare tumor among various pancreatic tumors and is generally observed in young women. Therefore, the identification of an SPN should be considered in cases where a solid/cystic mass is detected in the pancreas of a young woman. Distal pancreatectomy is performed for a large size of SPN located in the tail of the pancreas. Here, we report a 15-year-old Japanese female who brought about Type 3C diabetes mellitus (T3C-DM) after a distal pancreatectomy due to SPN. This case highlights the importance of management after pancreatectomy to detect early T3C-DM and prevent its development even in young patients. Although it is not surprising that a massive pancreatic tumor or pancreatectomy can lead to pancreatic diabetes at any age, we believe that it is important for clinicians to know this subject for educational purposes.